CORRELATION OF CENTRAL CORNEAL THICKNESS TO ACTUAL INTRAOCULAR PRESSURE IN MYOPIA PATIENTS - Pandjaitan, Hadwer Wicaksono; Ariesti, Andrini (Majalah Oftalmologi Indonesia, 2025)
Background : Central Corneal Thickness (CCT) is promote in the diagnosis and management of glaucoma, especially in myopic patients. Understanding the correlation between CCT and IOP (Intraocular Pressure) aids in glaucoma detection and control. The objective of this study is to determine the correlation between CCT and actual IOP in myopic patients. Methods : This research is an observational study with ethical committee approval, involving medical students from the Faculty of Medicine at Andalas University undergoing clinical clerkships at Dr. M Djamil Padang General Hospital. They were grouped into emmetropia, mild myopia, and moderate myopia. Data included visual acuity measurements, autorefraction, CCT measurements using OCT, and IOP with CCT correction. Samples with eye abnormalities, systemic conditions, myopia > 6D, a history of eye surgery, contact lens wear, and IOP > 21 mmHg were excluded. All data were analyzed statistically. Results : The study involved 78 eyes from 78 individuals, consisting of 26 eyes per group. The actual CCT and IOP values in mild myopia, moderate myopia and emmetropia are 506.31 ± 11,263 μm with 15.81 ± 1,234 mmHg, 533.96 ± 21,342 μm with 16.12 ± 1,336 mmHg, and 487.81 ± 28,272 μm with 15.35 ± 1.056 mmHg. There was a strong positive correlation between CCT and IOP (r=0.737, p=0.000), as well as a moderate negative correlation between CCT and actual IOP (r=-0.492, p=0.000). Conclusion : This research reveals a negative correlation between CCT and actual IOP in myopic patients, highlighting the importance of glaucoma screening for myopic patients due to their thinner corneas.